Secondary battery and electronic device
By using a combination of negative electrode materials and electrolytes with a specific specific surface area in the secondary battery, the storage performance and impedance enhancement of the secondary battery under high and low temperature conditions is solved, and more efficient battery performance is achieved.
Patent Information
- Application Number
- CN202411982987.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-04-01
AI Technical Summary
There is room for improvement in existing secondary batteries in terms of storage performance and impedance, especially under high and low temperature conditions.
The storage performance of the battery is improved and impedance is reduced by using a combination of negative electrode materials and electrolytes of a specific specific surface area in the secondary battery, including methyl ethyl carbonate and acryl-1,3-sulfonate lactone.
This technical method not only improves the high and low temperature storage performance of the secondary battery, but also significantly reduces the impedance of the battery, thereby improving the overall performance.
Smart Images

Figure BDA0005222702930000131 
Figure BDA0005222702930000141
Abstract
Description
[0001] This application is a divisional application of a patent application with an application date of November 5, 2024, application number 202411563066.1, and invention name “Secondary battery and electronic device”. Technical Field
[0002] The present application relates to the field of energy storage, and in particular to a secondary battery and an electronic device. Background Art
[0003] As a current application and research hotspot, secondary batteries have been widely commercialized in portable electronic devices, electric vehicles and other fields. However, with the update and iteration of various products and the continuous improvement of consumers' requirements for product performance, the further improvement of secondary battery storage performance and the reduction of impedance are still the focus issues that need to be solved urgently.
[0004] Existing secondary batteries are mainly composed of positive electrodes, negative electrodes and electrolytes. In order to meet people's increasingly high requirements, electrolytes are used as an important medium to soak the gaps between the active material particles on the positive and negative electrode sheets. Its innovative research is of great significance to the performance improvement of secondary batteries. Therefore, it is urgent to provide an electrolyte that can improve the storage performance of secondary batteries and reduce impedance. Summary of the invention
[0005] The present invention improves storage performance and reduces impedance by regulating the negative electrode material and electrolyte in the secondary battery. The inventor of the present invention found that the negative electrode includes a negative electrode current collector and a negative electrode material disposed on the negative electrode current collector, and the specific surface area of the negative electrode material is 1m 2 / g to 4m 2 / g, the electrolyte includes ethyl methyl carbonate and propenyl-1,3-sultone, relative to 100 parts by mass of the electrolyte, ethyl methyl carbonate is 65 parts by mass to 85 parts by mass, and propenyl-1,3-sultone is 0.01 parts by mass to 0.9 parts by mass, which can not only improve the high and low temperature storage performance of the battery, but also reduce the impedance, thereby completing the present application.
[0006] In some embodiments, the mass ratio of ethyl methyl carbonate to propenyl-1,3-sultone is (500-1000):1.
[0007] In some embodiments, the mass content ratio of ethyl methyl carbonate to propenyl-1,3-sultone is (600-900):1.
[0008] In some embodiments, the electrolyte includes lithium tetrafluoroborate, and the lithium tetrafluoroborate is present in an amount of 0.01 parts by mass to 0.8 parts by mass relative to 100 parts by mass of the electrolyte.
[0009] In some embodiments, the electrolyte includes lithium tetrafluoroborate, and the lithium tetrafluoroborate is in an amount of 0.03 parts by mass to 0.07 parts by mass relative to 100 parts by mass of the electrolyte.
[0010] In some embodiments, the electrolyte includes tetramethyl borate, and the amount of tetramethyl borate is 0.1 parts by mass to 0.4 parts by mass relative to 100 parts by mass of the electrolyte.
[0011] In some embodiments, the mass ratio of ethyl methyl carbonate to tetramethyl borate is (400-700):(1-2).
[0012] In some embodiments, the negative electrode material includes a silicon-based material.
[0013] In some embodiments, the silicon-based material includes a composite of a silicon-based substance and a carbon-based substance.
[0014] In another aspect of the present application, the present application provides an electronic device, which includes the secondary battery described in the present application.
[0015] The present application uses a combination of a specific negative electrode and an electrolyte, which can not only improve the high and low temperature storage performance of the secondary battery, but also reduce the impedance.
[0016] Additional aspects and advantages of the embodiments of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. DETAILED DESCRIPTION
[0017] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.
[0018] Unless expressly stated otherwise, the following terms used in this application have the meanings indicated below.
[0019] The present application uses a specific combination of a negative electrode and an electrolyte to not only improve the high and low temperature storage performance of the secondary battery but also reduce the impedance.
[0020] In one embodiment, the present application provides a secondary battery, which includes a positive electrode, a negative electrode, and an electrolyte as described below.
[0021] I. Electrolyte
[0022] The present application relates to a secondary battery and an electronic device. Specifically, the present application provides a secondary battery, which includes: a positive electrode, a negative electrode and an electrolyte. The electrolyte used in the secondary battery of the present application includes an electrolyte and a solvent for dissolving the electrolyte. The electrolyte includes ethyl methyl carbonate and propenyl-1,3-sultone. Relative to 100 parts by mass of the electrolyte, ethyl methyl carbonate is 65 parts by mass to 85 parts by mass, and propenyl-1,3-sultone is 0.01 parts by mass to 0.9 parts by mass. The negative electrode includes a negative electrode current collector and a negative electrode material disposed on the negative electrode current collector. The specific surface area of the negative electrode material is 1m 2 / g to 4m 2 / g.
[0023] When a specific content of ethyl methyl carbonate and propenyl-1,3-sultone is used in the secondary battery in the present application, the inventors found that the synergistic effect of the ethyl methyl carbonate and the negative electrode material with a specific specific surface area in the present application can not only improve the high and low temperature storage performance of the secondary battery, but also reduce the impedance. It is speculated that the reason may be that the specific content of ethyl methyl carbonate and propenyl-1,3-sultone can better infiltrate the negative electrode material with a specific surface area in the present application within the content range specified in the present application, and synergistically generate a negative electrode interface film, thereby improving the high and low temperature storage performance of the secondary battery and reducing the impedance.
[0024] Specifically, from the viewpoint of improving the high and low temperature storage performance of the secondary battery and reducing the impedance, the mass content ratio of ethyl methyl carbonate to propenyl-1,3-sultone is (500-1000):1, preferably (600-900):1.
[0025] Specifically, from the viewpoint of improving the high and low temperature storage performance of the secondary battery and reducing the impedance, the electrolyte includes lithium tetrafluoroborate (LiBF4), and the lithium tetrafluoroborate is 0.01 to 0.8 parts by mass, preferably 0.03 to 0.07 parts by mass, relative to 100 parts by mass of the electrolyte. When the above conditions are met, it helps to further improve the high and low temperature storage performance and reduce the impedance.
[0026] Specifically, in some embodiments, the electrolyte further includes tetramethyl borate, and the tetramethyl borate is 0.1 to 0.4 parts by mass relative to 100 parts by mass of the electrolyte. When the above conditions are met, it helps to further improve the high and low temperature storage performance of the secondary battery and reduce impedance.
[0027] Specifically, from the viewpoint of improving the high and low temperature storage performance of the secondary battery and reducing the impedance, the mass content ratio of ethyl methyl carbonate and tetramethyl borate is (400-700):(1-2).
[0028] In some embodiments, the electrolyte contains one or more of the following substances: ethylene glycol sulfate, 1,2-propylene glycol sulfate, 1,3-propylene glycol sulfate, 1,2-butylene glycol sulfate, 1,3-butylene glycol sulfate, 1,4-butylene glycol sulfate, 1,2-pentanediol sulfate, 1,3-pentanediol sulfate, 1,4-pentanediol sulfate, 1,5-pentanediol sulfate, dimethyl sulfate, ethyl methyl sulfate, methyl fluorosulfonate, ethyl trifluoromethanesulfonate, methyl methanesulfonate, ethyl methanesulfonate, butyl dimethanesulfonate, 2-(Methylsulfonyloxy)propionic acid methyl ester, 2-(Methylsulfonyloxy)propionic acid ethyl ester, 1-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, 3-fluoro-1,3-propane sultone, 1-methyl-1,3-propane sultone, 2-methyl-1,3-propane sultone, 3-methyl-1,3-propane sultone, 2-propylene-1,3-sultone, 1-fluoro-1-propylene-1,3-sultone, 2-fluoro-1-propylene-1,3-sultone, 3-fluoro-1-propylene-1,3 -sultone, 1-fluoro-2-propylene-1,3-sultone, 2-fluoro-2-propylene-1,3-sultone, 3-fluoro-2-propylene-1,3-sultone, 1-methyl-1-propylene-1,3-sultone, 2-methyl-1-propylene-1,3-sultone, 3-methyl-1-propylene-1,3-sultone, 1-methyl-2-propylene-1,3-sultone, 2-methyl-2-propylene-1,3-sultone, 3-methyl-2-propylene-1,3-sultone, 1,4 -Butane sultone, 1,5-pentane sultone, methylene methanedisulfonate, ethylene methanedisulfonate, dimethyl sulfite, ethyl methyl sulfite, lithium difluorophosphate, 1,2-ethylene glycol sulfite, 1,2-propylene glycol sulfite, 1,3-propylene glycol sulfite, 1,2-butylene glycol sulfite, 1,3-butylene glycol sulfite, 1,4-butylene glycol sulfite, 1,2-pentanediol sulfite, 1,3-pentanediol sulfite, 1,4-pentanediol sulfite, 1,5-pentanediol sulfite, etc.
[0029] In some embodiments, the electrolyte further includes an ionizable lithium salt, and the ionizable lithium salt includes at least one of LiPF6, LiSbF6, LiAsF6, LiClO4, LiN(C2F5SO2)2, CF3SO3Li, LiC(CF3SO2)3 or LiC4BO8. For example, the lithium salt used in the electrolyte of the present application includes LiPF6, and the content of LiPF6 is 9 to 15% by mass, preferably 9 to 13% by mass, and more preferably 9 to 12% by mass based on the mass of the electrolyte. By setting the above content range, the cycle performance and safety of the secondary battery can be further improved.
[0030] In some embodiments, the electrolyte further includes at least one of lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), and lithium bis(fluorosulfonyl imide) (LiFSI).
[0031] In some embodiments, the additive in the electrolyte further includes at least one of a fluoroether compound, a fluorocarbonate compound, and an ether nitrile compound, such as hydrofluoroether (HFE-458), fluoroethylene carbonate (FEC), and the like.
[0032] In some embodiments, the electrolyte may further include a non-aqueous solvent. The non-aqueous solvent may be selected from carbonate compounds, carboxylate compounds, ether compounds, phosphate compounds, other organic solvents, or combinations thereof.
[0033] Optionally, the carbonate compound may be a linear carbonate compound, a cyclic carbonate compound or a combination thereof. On the other hand, the carbonate compound may also be a fluorinated carbonate compound, a non-fluorinated carbonate compound or a combination thereof.
[0034] Specifically, examples of chain carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.
[0035] Specifically, examples of the carboxylate compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.
[0036] Specifically, examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.
[0037] Specifically, examples of the phosphate compound are trimethyl phosphate, triethyl phosphate, trioctyl phosphate, or a combination thereof.
[0038] Specifically, examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methylpyrrolidone, formamide, dimethylformamide, acetonitrile, or a combination thereof.
[0039] II. Negative electrode
[0040] The negative electrode includes a negative electrode current collector and a negative electrode material disposed on the surface of the negative electrode current collector. The specific surface area of the negative electrode material in this application is 1 m 2 / g to 4m 2 / g.
[0041] In some embodiments, the charge capacity of the negative electrode material is greater than the discharge capacity of the positive electrode material to prevent unintentional precipitation of lithium metal on the negative electrode during charging.
[0042] In some embodiments, the negative electrode material includes a carbon-based negative electrode material, a metal-based negative electrode material, and a negative electrode material combining the carbon-based negative electrode material and the like.
[0043] Carbon-based negative electrode materials
[0044] Here, the carbon-based negative electrode material refers to an active material having a carbon-based skeleton into which lithium can be inserted, and examples of the carbon-based negative electrode material include carbonaceous materials and graphite materials.
[0045] As carbonaceous materials, for example, graphitizable carbon, non-graphitizable carbon having a structure similar to an amorphous structure represented by glassy carbon, etc. can be cited. Here, as graphitizable carbon, for example, carbon materials obtained from petroleum or coal using tar pitch as a raw material can be cited. When giving specific examples, coke, mesocarbon microbeads (MCMB), mesophase pitch-based carbon fibers, and pyrolysis vapor-grown carbon fibers can be cited. In addition, as non-graphitizable carbon, for example, phenolic resin sintered bodies, polyacrylonitrile-based carbon fibers, quasi-isotropic carbon, furfuryl alcohol resin sintered bodies (PFA), hard carbon, etc. can be cited.
[0046] Furthermore, as graphite materials, for example, natural graphite, artificial graphite, etc. can be cited. Among them, as artificial graphite, for example: artificial graphite obtained by heat-treating carbon containing graphitized carbon mainly at 2800°C or above, graphite MCMB obtained by heat-treating MCMB at 2000°C or above, graphite mesophase pitch-based carbon fiber obtained by heat-treating mesophase pitch-based carbon fiber at 2000°C or above, etc. can be cited. In addition, in the present application, as a carbon-based negative electrode material, natural graphite (amorphous coated natural graphite) in which at least a portion of its surface is coated with amorphous carbon can be used.
[0047] In addition, the metal-based negative electrode material is an active material containing a metal, and generally refers to an active material that contains an element capable of inserting lithium or alloying with lithium in its structure and has a theoretical current capacity of 500 mAh / g or more per unit mass when lithium is inserted or alloyed with lithium. As the metal-based negative electrode material, for example, lithium metal, elemental metals capable of forming a lithium alloy (such as Ag, Al, Ba, Bi, Cu, Ga, Ge, In, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, etc.) and their alloys, as well as their oxides, sulfides, nitrides, silicides, carbides, phosphides, etc. can be used. Among them, as the metal-based negative electrode material, an active material containing silicon (silicon-based negative electrode material) is preferred. This is because the use of a silicon-based negative electrode material can increase the capacity of the secondary battery.
[0048] In some embodiments, the negative electrode material includes a silicon-based material.
[0049] In some embodiments, the silicon-based material includes at least one of a composite of a silicon-based substance and a carbon-based substance or a silicon oxide (SiO x , 0 < x ≤ 2). The silicon-based substance can be silicon particles, silicon alloy particles, or a silicon oxide (SiO x , 0 < x ≤ 2), etc. The negative electrode material may further include a carbon material, and the carbon material can be crystalline carbon, amorphous carbon, or a mixture thereof. The crystalline carbon can be graphite, such as amorphous, plate-shaped, flaky, spherical, or fibrous natural graphite and / or artificial graphite, and the amorphous carbon can be soft carbon (low-temperature calcined carbon), hard carbon, mesophase pitch carbide, or calcined coke, etc.
[0050] The composite of the silicon-based substance and the carbon-based substance can be a composite having a structure in which silicon nanoparticles are arranged on the carbon-based substance, a composite in which silicon particles are included on the surface and inside of the carbon-based substance, and a composite in which the silicon particles are coated with the carbon-based substance and included in the carbon-based substance. In the composite of the silicon-based substance and the carbon-based substance, the carbon-based substance can be graphite, graphene, graphene oxide, or a combination thereof.
[0051] The composite of silicon-based substances and carbon-based substances may be an active material obtained by dispersing silicon nanoparticles having an average particle size of 200nm or less on carbon-based substance particles, and then coating with carbon, an active material in which silicon (Si) particles are present on and inside graphite, etc. The average particle size of the secondary particles of the composite of silicon-based substances and carbon-based substances may be 5μm to 20μm. The average particle size of the silicon nanoparticles may be 5nm or more, for example, 10nm or more, for example, 20nm or more, for example, 50nm or more, for example, 70nm or more. The average particle size of the silicon nanoparticles may be 200nm or less, 150nm or less, 100nm or less, 50nm or less, 20nm or less, or 10nm or less. For example, the average particle size of the silicon nanoparticles may be 100nm to 150nm.
[0052] The secondary particles of the composite of the silicon-based substance and the carbon-based substance may have an average particle size of 5 μm to 20 μm, for example, 7 μm to 15 μm, for example, 10 μm to 13 μm.
[0053] From the viewpoint of improving battery capacity, a silicon-carbon material, for example, a porous carbon-supported silicon composite material is preferred.
[0054] The negative electrode material may be used alone or in combination of two or more at any ratio.
[0055] In some embodiments, the specific surface area of the negative electrode material is 1 m 2 / g to 4m 2 / g.
[0056] Here, the volume average particle size of the negative electrode material is preferably 1 μm or more, more preferably 5 μm or more, preferably 30 μm or less, and more preferably 20 μm or less. If the volume average particle size of the negative electrode material is above the above lower limit, the heat generation during the internal short circuit can be effectively suppressed. In addition, if the volume average particle size of the negative electrode material is below the above upper limit, the increase in the initial resistance of the obtained battery can be effectively suppressed.
[0057] The negative electrode material layer may further include a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode material particles and the bonding between the negative electrode material and the current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the electrolyte or electrode manufacturing. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.
[0058] As a current collector for maintaining the negative electrode material, any known current collector can be used. Examples of negative electrode current collectors include, but are not limited to, metal materials such as copper, nickel, stainless steel, and nickel-plated steel. In some embodiments, the negative electrode current collector is copper. In some embodiments, the negative electrode current collector is a composite current collector, i.e., a 12 μm composite copper foil (commercially available, a composite current collector made of polyethylene terephthalate (PET) as a base material and depositing a metal copper layer on both sides thereof using an advanced vacuum coating process).
[0059] The negative electrode can be prepared by applying a negative electrode mixture slurry containing a negative electrode material, a resin binder, etc. on a negative electrode current collector, drying it, and then rolling it to form a negative electrode material layer on both sides of the negative electrode current collector, thereby obtaining a negative electrode.
[0060] III. Positive electrode
[0061] The positive electrode includes a positive electrode collector and a positive electrode material disposed on a surface of the positive electrode collector.
[0062] The positive electrode material can be one layer or multiple layers. Each layer of the multiple layers of positive electrode material can contain the same or different positive electrode active materials. The positive electrode active material is any material that can reversibly embed and de-embed lithium ions.
[0063] The positive electrode active material includes a lithium transition metal oxide containing nickel and other transition metals. In the lithium transition metal oxide including nickel and other transition metals, the amount of nickel relative to the total molar number of the transition metal may be 60 mol% or more, for example, 75 mol% or more, for example, 80 mol% or more, for example, 85 mol% or more, or for example, 90 mol% or more.
[0064] For example, the lithium transition metal oxide may be a compound represented by the following Formula 1:
[0065] Formula 1: Li a Ni x Co y M z O 2-b A b ,
[0066] Wherein, in formula 1, 0.9≤a≤1.2, 0≤b≤0.2, 0.6≤x<1, 0<y≤0.3, 0<z≤0.3, and x+y+z=1, M is at least one selected from manganese (Mn), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al) or boron (B), and A is F, S, Cl, Br or a combination thereof. For example, the above subscripts may be 0.7≤x<1, 0<y≤0.3, and 0<z≤0.3; 0.8≤x<1, 0<y≤0.3, and 0<z≤0.3; 0.8≤x<1, 0<y≤0.2, and 0<z≤0.2; 0.83≤x<0.97, 0<y≤0.15, and 0<z≤0.15; or 0.85≤x<0.95, 0<y≤0.1, and 0<z≤0.1.
[0067] For example, the lithium transition metal oxide may be at least one compound represented by Formula 2 or Formula 3 below:
[0068] Formula 2: LiNi x Co y Mn z O2,
[0069] In Formula 2, 0.6≤x≤0.95, 0<y≤0.2, and 0<z≤0.1, for example, 0.7≤x≤0.95, 0<y≤0.3, and 0<z≤0.3.
[0070] Formula 3: LiNi x Co y Al z O2,
[0071] Wherein, in Formula 3, 0.6≤x≤0.95, 0<y≤0.2, and 0<z≤0.1, for example, 0.7≤x≤0.95, 0<y≤0.3, and 0<z≤0.3, for example, 0.8≤x≤0.95, 0<y≤0.3, and 0<z≤0.3, for example, 0.82≤x≤0.95, 0<y≤0.15, and 0<z≤0.15, for example, 0.85≤x≤0.95, 0<y≤0.1, and 0<z≤0.1.
[0072] For example, the lithium transition metal oxide may be LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.88 Co 0.08 Mn 0.04 O2、LiNi 0.8 Co 0.15 Mn 0.05O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.88 Co 0.1 Mn 0.02 O2、LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2 or LiNi 0.88 Co 0.1 Al 0.02 O2.
[0073] According to another embodiment, the positive electrode active material includes at least one active material selected from the group consisting of Li-Ni-Co-Al (NCA), Li-Ni-Co-Mn (NCM), lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMnO2), lithium nickel oxide (LiNiO2) and lithium iron phosphate (LiFePO4).
[0074] In some embodiments, the type of positive electrode conductive material is not limited, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.
[0075] There is no particular restriction on the type of positive electrode binder used in the manufacture of positive electrode materials. In the case of a coating method, any material that can be dissolved or dispersed in the liquid medium used in the manufacture of the electrode can be used. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber polymers such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, polybutadiene rubber, and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or their hydrogenates, ethylene-propylene-diene terpolymers (EPDM), Thermoplastic elastomer polymers such as styrene·ethylene·butadiene·ethylene copolymers, styrene·isoprene·styrene block copolymers or their hydrogenated products; soft resin polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene·vinyl acetate copolymers, propylene·α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene·ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions (especially lithium ions), etc. The above positive electrode binders can be used alone or in any combination.
[0076] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, a mixed medium of alcohol and water or water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.
[0077] Thickeners are generally used to adjust the viscosity of the slurry. In the case of using an aqueous medium, a thickener and a styrene-butadiene rubber (SBR) emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The above thickeners may be used alone or in any combination.
[0078] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0079] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode material, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings may include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.
[0080] The positive electrode can be made by forming a positive electrode material containing a positive electrode active material and a binder on a current collector. The manufacture of a positive electrode using a positive electrode active material can be carried out by a conventional method, that is, the positive electrode active material and the binder, as well as the conductive material and the thickener as required, are dry-mixed to form a sheet, and the obtained sheet is pressed onto the positive electrode current collector; or these materials are dissolved or dispersed in a liquid medium to form a slurry, and the slurry is applied to the positive electrode current collector and dried to form a positive electrode material on the current collector, thereby obtaining a positive electrode.
[0081] IV. Isolation membrane
[0082] In order to prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode. In this case, the electrolyte of the present application is usually used by infiltrating the separator.
[0083] There is no particular restriction on the material and shape of the isolation membrane, as long as the effect of the present application is not significantly impaired. The isolation membrane may be a resin, glass fiber, inorganic substance, etc. formed of a material that is stable to the electrolyte of the present application. In some embodiments, the isolation membrane includes a porous sheet or a non-woven fabric-like material with excellent liquid retention. Examples of materials for resin or glass fiber isolation membranes may include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above isolation membranes may be used alone or in any combination.
[0084] The isolation film may also be a material formed by laminating the above materials, and examples thereof include, but are not limited to, a three-layer isolation film formed by laminating polypropylene, polyethylene, and polypropylene in this order.
[0085] Examples of inorganic materials may include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates (e.g., barium sulfate, calcium sulfate, etc.) The form of the inorganic material may include, but is not limited to, granular or fibrous.
[0086] The separator may be in the form of a thin film, examples of which include, but are not limited to, nonwoven fabrics, woven fabrics, microporous films, etc. In the thin film form, the separator has a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film separators, the following separators may also be used: a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin-based adhesive, for example, a separator formed by using a fluororesin as an adhesive to form a porous layer on both sides of the positive electrode with aluminum oxide particles having a particle size of 90% less than 1 μm.
[0087] The thickness of the isolation film is arbitrary. In some embodiments, the thickness of the isolation film is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the isolation film is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the isolation film is within the above range, the insulation and mechanical strength can be ensured, and the DC resistance characteristics and energy density of the secondary battery can be ensured.
[0088] The present application further provides an electronic device, which includes the secondary battery described in the present application.
[0089] The use of the secondary battery of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the secondary battery of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0090] Example
[0091] Examples of the secondary battery of the present application are shown below, but the present application is not limited to these examples.
[0092] Preparation of secondary batteries
[0093] Production of positive electrode:
[0094] LiNi 0.88 Co 0.08 Mn 0.04O2 positive electrode material (97wt%), conductive carbon black (1.5wt%), and polyvinylidene fluoride (1.5wt%) are dissolved in N-methylpyrrolidone and mixed to prepare a positive electrode slurry. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and the aluminum foil is dried at 120°C to obtain a positive electrode sheet coated with a positive electrode material layer with a thickness of 80μm on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. The coated aluminum foil is dried, pressurized, and cut into a specified size to make a positive electrode.
[0095] Isolation film: A 12 μm thick polyethylene (PE) microporous membrane was selected as the isolation membrane.
[0096] Negative electrode production:
[0097] A negative electrode material (96 wt%) and styrene-butadiene rubber (2 wt%) were mixed and added to a solution prepared by dissolving 2 wt% of lithium carboxymethyl cellulose in deionized water and mixed to prepare a negative electrode slurry. The negative electrode slurry was coated on one side of a copper foil (except for the composite copper foil used in Examples 11 and 12, the rest were conventional copper foils), dried, pressurized, and then cut into a specified size to prepare a negative electrode.
[0098] The present application has no particular restrictions on the method for regulating the specific surface area of the negative electrode material, as long as the purpose of the present application can be achieved. For example, negative electrode materials with different specific surface areas can be obtained by mechanical crushing, grinding, screening, etc. Exemplarily, negative electrode materials with different specific surface areas can be obtained by ball milling in mechanical crushing. Generally, the specific surface area increases with the extension of ball milling time, and the specific surface area decreases with the shortening of ball milling time.
[0099] Preparation of electrolyte: In an argon atmosphere glove box with a water content of less than 10ppm, ethyl methyl carbonate (content is subject to Table 1), dimethyl carbonate and ethylene carbonate (dimethyl carbonate and ethylene carbonate are in a mass ratio of 0.5:1) are mixed to obtain a base solvent, and then lithium salt LiPF6 and propenyl-1,3-sultone in an amount shown in Table 1 are added to the above base solvent (lithium tetrafluoroborate and / or tetramethylborate are also added in some embodiments, specific content is subject to Table 1), and the electrolyte is obtained after mixing evenly, wherein the mass content of LiPF6 is 12% based on the mass of the electrolyte.
[0100] Battery production:
[0101] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound, and the electrode assembly is placed in the outer packaging aluminum plastic film after welding the pole ear, and the water is removed at 80°C, and the above electrolyte is injected, and the lithium ion battery is obtained after vacuum packaging, standing, formation, shaping, capacity testing and other processes. The secondary battery is a bag-shaped battery with a width of 30mm, a height of 45mm, and a thickness of 5mm.
[0102] Table 1
[0103]
[0104]
[0105] Test Method
[0106] Specific surface area
[0107] The test method is as follows:
[0108] The specific surface area of the negative electrode materials of each embodiment and comparative example was tested by nitrogen adsorption using a specific surface area analyzer (Tristar II 3020M). The specific test was performed in accordance with the national standard GB / T19587-2017 "Determination of the specific surface area of solid substances by gas adsorption BET method".
[0109] Battery storage performance
[0110] The test method is as follows:
[0111] Place the lithium-ion battery in a 15℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 0.7C to a voltage of 4.3V, and then charge it at a constant voltage of 4.3V to a current of 82.5mA. Test the thickness of the lithium-ion battery and record it as T0; place it in a 45℃ oven for 10 hours, take it out of the oven and cool it for 1 hour, test the thickness of the lithium-ion battery as T1, and monitor the thickness of the lithium-ion battery in the oven in real time.
[0112] The storage thickness expansion rate at 45°C is calculated by the following formula:
[0113] 45°C storage thickness expansion ratio = (T1-T0) / T0×100%.
[0114] The evaluation was performed according to the following criteria: the smaller the thickness expansion rate, the better the high and low temperature storage performance of the secondary battery in the present application.
[0115] A: Thickness expansion ratio is less than 12%.
[0116] B: The thickness expansion ratio is 12% or more and less than 15%.
[0117] C: The thickness expansion ratio is 15% or more and less than 20%.
[0118] D: The thickness expansion ratio is 20% or more.
[0119] impedance
[0120] The test method is as follows:
[0121] At 15°C, the lithium-ion battery is charged to 4.3V at 0.7C constant current, then charged to 82.5mA at 4.3V constant voltage, and then discharged at 0.2C constant current for 4h, so that the lithium-ion battery state of charge (SOC) is 20%. Discharge at 0.1C for 10s to obtain voltage V0; discharge at 1C for 1s to obtain voltage V1. DCR (initial state at 15°C) = (V0-V1) / 0.1C.
[0122] Place the lithium-ion battery in a 45°C constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature to 4.3V at 0.7C constant current at 45°C, then charge it to 82.5mA at 4.3V constant voltage, and then discharge it to 3.0V at 0.2C constant current. This is a charge and discharge cycle. After 800 cycles of charge / discharge, charge the lithium-ion battery to 4.3V at 0.7C constant current, then charge it to 82.5mA at 4.3V constant voltage, and then discharge it at 0.2C constant current for 4h, so that the lithium-ion battery state of charge (SOC) is 20%. Discharge at 0.1C for 10s to obtain a voltage of V2; discharge at 1C for 1s to obtain a voltage of V3. DCR (45°C 800 cycles) = (V2-V3) / 0.1C.
[0123] The 45°C cycle DCR change rate is calculated by the following formula:
[0124] Cycle DCR change rate = (DCR (800 cycles at 45°C) / DCR (initial state at 15°C) - 1) × 100%.
[0125] The evaluation was performed according to the following criteria: the smaller the impedance, the better the performance of the secondary battery.
[0126] A: The DCR change rate is less than 25%.
[0127] B: The DCR change rate is 25% or more and less than 29%.
[0128] C: The DCR change rate is 29% or more and less than 35%.
[0129] D: The DCR change rate is 35% or more.
[0130] Test Results
[0131] In Table 1, “ / ” indicates that the substance was not added;
[0132] It can be seen from Table 1 that the negative electrode of the present application includes a negative electrode current collector and a negative electrode material disposed on the negative electrode current collector, and the specific surface area of the negative electrode material is 1m 2 / g to 4m 2 / g, the electrolyte includes ethyl methyl carbonate and propenyl-1,3-sultone. Relative to 100 parts by mass of the electrolyte, the ethyl methyl carbonate is 65 parts by mass to 85 parts by mass, and the propenyl-1,3-sultone is 0.01 parts by mass to 0.9 parts by mass, which can not only improve the high and low temperature storage performance of the battery, but also reduce the impedance.
[0133] In particular, the mass content ratio of ethyl methyl carbonate to propenyl-1,3-sultone is (500-1000):1, which can further improve the high and low temperature storage performance of the secondary battery and reduce the impedance.
[0134] In particular, the mass content ratio of ethyl methyl carbonate to propenyl-1,3-sultone is (600-900):1, which can further improve the high and low temperature storage performance of the secondary battery and reduce the impedance.
[0135] In particular, the electrolyte includes lithium tetrafluoroborate, and the lithium tetrafluoroborate is 0.01 to 0.8 parts by mass relative to 100 parts by mass of the electrolyte, which can further improve the high and low temperature storage performance of the secondary battery and reduce impedance.
[0136] In particular, the electrolyte includes lithium tetrafluoroborate, and the lithium tetrafluoroborate is 0.03 to 0.07 parts by mass relative to 100 parts by mass of the electrolyte, which can further improve the high and low temperature storage performance of the secondary battery and reduce impedance.
[0137] In particular, the electrolyte includes tetramethyl borate, and the tetramethyl borate is 0.1 to 0.4 parts by mass relative to 100 parts by mass of the electrolyte, which can further improve the high and low temperature storage performance of the secondary battery and reduce impedance.
[0138] In particular, the mass content ratio of ethyl methyl carbonate and tetramethyl borate is (400-700):(1-2), which can further improve the high and low temperature storage performance of the secondary battery and reduce the impedance.
[0139] In particular, the negative electrode material includes silicon-based materials, which can further improve the high and low temperature storage performance of the secondary battery and reduce impedance.
[0140] In particular, silicon-based materials include composites of silicon-based substances and carbon-based substances, which can further improve the high and low temperature storage performance of secondary batteries and reduce impedance.
[0141] References to "embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics in the present application may be combined in one or more embodiments or examples in any suitable manner.
[0142] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. A secondary battery comprising: A positive electrode, a negative electrode and an electrolyte, characterized in that The negative electrode comprises a negative electrode current collector and a negative electrode material disposed on the negative electrode current collector, wherein the specific surface area of the negative electrode material is 1 m 2 / g to 4m 2 / g; The electrolyte comprises ethyl methyl carbonate and propenyl-1,3-sultone, wherein the ethyl methyl carbonate is 65 to 85 parts by mass, and the propenyl-1,3-sultone is 0.01 to 0.9 parts by mass relative to 100 parts by mass of the electrolyte; The electrolyte solution includes lithium tetrafluoroborate, and the lithium tetrafluoroborate is present in an amount of 0.01 to 0.8 parts by mass relative to 100 parts by mass of the electrolyte solution.
2. The secondary battery according to claim 1, characterized in that: The mass content ratio of the ethyl methyl carbonate to the propenyl-1,3-sultone is (500-1000):
1.
3. The secondary battery according to claim 1, characterized in that: The mass content ratio of the ethyl methyl carbonate to the propenyl-1,3-sultone is (600-900):
1.
4. The secondary battery according to claim 1, characterized in that: The lithium tetrafluoroborate is contained in an amount of 0.03 to 0.07 parts by mass relative to 100 parts by mass of the electrolyte.
5. The secondary battery according to any one of claims 1 to 3, characterized in that: The electrolyte solution includes tetramethyl borate, and the tetramethyl borate is in an amount of 0.1 to 0.4 parts by mass relative to 100 parts by mass of the electrolyte solution.
6. The secondary battery according to claim 5, characterized in that: The mass content ratio of the ethyl methyl carbonate to the tetramethyl borate is (400-700):(1-2).
7. The secondary battery according to any one of claims 1 to 3, characterized in that: The negative electrode material includes a silicon-based material.
8. The secondary battery according to claim 7, characterized in that: The silicon-based material includes a composite of a silicon-based substance and a carbon-based substance.
9. An electronic device, characterized in that: It includes the secondary battery according to any one of claims 1 to 8.
Citation Information
Cited By
Secondary battery and electronic device
WO2026098063A1